Penentuan Nilai Sun Protection Factor (SPF) Nanoemulgel Ekstrak Daun Keji Beling dan Kelor - Anindita, Reza Anindita; Uzia Beandrade, Maya; Kurnia Putri, Intan; Dwi Nathalia, Dede (JURNAL BIOSHELL, 2023)
The incidence of skin cancer was found to be 5.9% -7.8% spread across various hospitals or the third position for most cancers after cervical and breast cancer. One solution to prevent skin cancer is the use of sunscreen or sunscreen. The purpose of this study was to determine the SPF value of nanoemulgel ethanol extract of keji beling and kelor leaves. This type of research is quantitative. The samples used were keji beling and kelor leaf extracts. The extraction method is maceration with 96% ethanol solvent. Testing the SPF value using the spectrophotometric method with a wavelength of 290-320 nm with an increase of 5 nm intervals. The results of this study showed that the best nanoemulgel value was found in formula 1 (F1) 5% of 42.17. The SPF value with a concentration of 3% is 12.19 (maximum protection category), 4% is 15.46 (ultra category), and 5% is 11.33 (maximum category). The conclusion from the study of nanoemulgel extracts of keji beling and kelor leaves has the potential to be used as a sunscreen preparation.